Management of Allergic Reactions to Contrast Media in Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) - sirocchi, luca (Journal of Advanced Health Care, 2024)
This study examines the best practices for managing allergic reactions to contrast media used in CT and MRI. The iodine- and gadolinium-based contrast agents commonly used to enhance the quality of diagnostic images can cause adverse reactions of varying severity. This article provides an overview of preventive strategies, intra-procedural and post-procedural management, as well as recommendations for future planning and patient education. Additionally, the role of prophylaxis and the importance of involving anesthesiologists in emergency situations are discussed